Factors associated with development of high-grade squamous intraepithelial lesions of the uterine cervix in women younger than 30 years - Jongpeeti Wudtisan (2019)
© 2019 Asian Pacific Organization for Cancer Prevention. Objective: To determine the factors associated with the increased risk of developing high-grade squamous intraepithelial lesions (HSIL) of the uterine cervix in women younger than 30 years compared with those aged ≥ 30 years who also had HSIL. Methods: Patients with HSIL who underwent loop electrosurgical excision procedure (LEEP) between January 2006 and July 2017 at Chiang Mai University Hospital were retrospectively reviewed. We analyzed the factors associated with the development of HSIL by comparing two age groups between women aged < 30 years and those aged ≥ 30 years. The factors analyzed included the well-recognized risk factors for cervical cancer, i.e. age at sexual debut, number of sexual partners, use of oral contraceptive (OC) pills, smoking history, sexually transmitted diseases and HIV status. Univariate and multivariate logistic regressions were used to assess factors associated with the increased risk of developing HSIL in women younger than 30 years compared with those aged ≥ 30 years. Results: During the study period, there were 345 patients with HSIL, 30 were < 30 years (case group) and 315 aged ≥ 30 years (control group). By multivariate analyses, early sexual debut(OR, 2.86; 95% CI, 1.01-8.13; P=0.047), multiple sexual partners (OR, 2.94; 95% CI, 1.23-7.02; P=0.015), history of genital warts (OR, 20.46; 95% CI, 2.27-183.72; P=0.007) and history of smoking (OR, 2.95; 95% CI, 1.10-7.93; P=0.032) were significantly associated with the development of HSIL in women younger than 30 years when compared with those aged ≥ 30 years. The OC use, HIV status and underlying diseases were not significantly different in both groups. Conclusion: Early age at sexual debut, multiple sexual partners, history of genital warts and smoking are significant risk factors for developing HSIL in women younger than 30 years. Cervical cancer screening should be considered in young women with such factors.